Design of Motor Development Stimulation Mattress for Low-Birth-Weight Babies - Eviana Tambunan; Ahmad Syakib; Christina Natalia Devina (Jurnal Ilmu dan Teknologi Kesehatan)
A mattress is one of the tools used to stimulate a baby's motor development. However, the mattresses currently on the market cannot stimulate a baby's movement, which emphasises the ability to control the head or neck stability and maintain a stable body. Based on these problems, a mattress aid was developed to improve the movement ability of babies with low birth weight (LBW) and facilitate the components of LBW development in the first six months. Objective: produce tool stimulation motion (prototype), namely a stimulation mat for stimulating the growth of baby motor skills LBW. The method used in making a stimulation mattress prototype is divided into five stages: preparation, design, expert validation, tool creation and testing. The prototype produced is a stimulation mattress with a wavy design to make it easier for babies to breathe when lying on their stomachs or prevent suffocation (because the nostrils are closed). The front of the mattress is slightly high to facilitate the baby lifting his head when lying on his stomach. The test results on LBW showed that the baby could easily roll over because the mattress position was down and bumpy. Conclusion: The undulating position of the mattress stimulates the baby's ability to control the head and, at the same time, can facilitate the baby's ability to roll over.